Ultrahigh-Field MR (7 T) Imaging of Brain Lesions in Neuromyelitis Optica. (27th January 2013) - Kister, Ilya; Herbert, Joseph; Zhou, Yongxia; Ge, Yulin
Abstract : Background . Brain lesions are common in neuromyelitis optica spectrum disorder (NMOsd) and may resemble lesions of multiple sclerosis (MS). Objectives . To describe the imaging characteristics of supratentorial lesions in NMOsd on ultrahigh-field (7 T) MRI with special attention to vessel-lesion relationship. Methods . Ten NMOsd patients, all women and all seropositive for NMO IgG, with mean age of 51.3 ± 15.4 years and disease duration of 9.2 ± 6.4 years, were scanned at a 7 T whole-body human MR system with high-resolution 2D gradient echo sequence optimized to best visualize lesions and venous structures, T2- and T1-weighted imaging. Results . In 10 patients with NMOsd, a total of 92 lesions were observed (mean: 9.2 ± 8.8; range: 2–30), but only 8 lesions (9%) were traversed by a central venule. All lesions were <5 mm in diameter, and 83% were located in subcortical white matter. There were no lesions in the cortex or basal ganglia. Two patients exhibited diffuse periependymal abnormalities on FLAIR. Conclusions . Small, subcortical lesions without a central venule are the most consistent finding of NMOsd on 7 T MRI of the brain. Ultrahigh-field imaging may be useful for differentiating between NMOsd and MS.